2000
DOI: 10.1161/01.cir.102.14.1671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Artery Stenting on Renal Function and Size in Patients with Atherosclerotic Renovascular Disease

Abstract: In patients with chronic renal insufficiency and global obstructive atherosclerotic renovascular disease, renal artery stenting improves or stabilizes renal function and preserves kidney size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(147 citation statements)
references
References 32 publications
3
137
1
4
Order By: Relevance
“…PTRA could therefore well be attempted before considering surgical intervention on patients with solitary functioning kidneys. [5][6][7][8] In patients with chronic renal insufficiency and global obstructive atherosclerotic vascular disease, PTRA and stenting of renal artery stenosis has been shown to improve or stabilise renal function and to preserve kidney size, 9 and Shannon et al 10 have advocated stenting as a relatively safe procedure to salvage a solitary kidney. Repeated PTRA and stent placement have previously been reported to be effective treatment for total RAO after prior unsuccessful balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…PTRA could therefore well be attempted before considering surgical intervention on patients with solitary functioning kidneys. [5][6][7][8] In patients with chronic renal insufficiency and global obstructive atherosclerotic vascular disease, PTRA and stenting of renal artery stenosis has been shown to improve or stabilise renal function and to preserve kidney size, 9 and Shannon et al 10 have advocated stenting as a relatively safe procedure to salvage a solitary kidney. Repeated PTRA and stent placement have previously been reported to be effective treatment for total RAO after prior unsuccessful balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the degree of arterial stenosis in ARAS does worsen with time, and renal function in patients with ARAS often deteriorates over time (12). In reality, however, the renal function decline seen in ARAS owes more to chronic massive ischemia (16) or atherosclerotic nephropathy-both of which are related to age, scarring, micro-embolisation and hypertension (17). A complex interaction develops between main vessel occlusive disease and microvascular injury, in part associated with cholesterol and activation of the oxidative pathway (18).…”
Section: <0014mentioning
confidence: 99%
“…A study carried out by Jensen 24 evaluated 107 patients with ARAS in a one-year follow-up after stenting in renal artery and found that this group showed decreased BP and increased glomerular filtration rate. Watson 25 also noticed the repercussion of stent angioplasty in the renal function of 33 patients with azotemia for 20 months (mean follow-up) and reported that the deteriorating renal function had stabilized or improved after the procedure. The number of daily doses of each drug were not evaluated.…”
Section: Discussionmentioning
confidence: 99%